Tourism Persistence in the Southeastern European Countries: The Impact of Covid-19 - Guglielmo Maria Caporale; Amir Imeri; Luis A. Gil-Ala\~na (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper examines tourism persistence in a group of Southeastern European (SEE) countries (Albania, Bosnia, Bulgaria, Croatia, Montenegro, North Macedonia, Serbia and Slovenia) by applying fractional integration methods to monthly data on foreign tourist arrivals and overnight stays. The results indicate that the COVID-19 pandemic has increased the degree of persistence of the series examined and also reduced the importance of their seasonal component.
Keywords: C13; C22; L83; N74; Z32; 330; SEE; Covid-19; fractional integration; persistence; shocks; tourism